Strengthening of Soil Slope by Berms - Kumar Bhat, Arun; ., . (International Journal of Engineering and Technology, 2018)
Slopes are part and parcel of every construction. The construction of residential building or roads or railways all needs embankments or cutting. The stability of these slopes is a major concern for all geotechnical engineers since they can be catastrophic if it fails. The slope stability is affected by various factors like slope angle, index properties of soil, drainage conditions etc.The stability of slope can be increased by providing geotextile or any other suitable reinforcement or by appropriate ground improvement techniques. The stability can also be increased by providing a horizontal berm which effectively divide a single slope in to two slopes. The modification in factor of safety by the introduction of berm is studied in this paper.The berm width is varied and the factor of safety is evaluated using Swedish method of slices. The effect of different berm width on three different slope angles are evaluated. The optimum location of berm is also evaluated for a selected berm width. The berm of sufficient width improves the stability of the slope. A berm width about 0.2 to 0.25 times the total height of slope located at mid height of slope is found to provide optimum factor of safety.Â